Pengaruh Economic Value Added dan Market Value Added terhadap Return Saham - Syifa Siti Nurfaizah; Azib (Bandung Conference Series: Business and Management, 2022)
Abstract. This study was conducted to determine the development of EVA, MVA, Stock Return and the effect of Economic Value Added and Market Value Added on stock returns in food and beverage manufacturing companies listed on the Indonesian stock exchange for the 2017-2020 period, either partially or simultaneously. The independent variables in this study are Economic Value Added (EVA) and Market Value Added (MVA), while the dependent variable is stock returns. The research method used is a quantitative method, with panel data regression using the common effects method which is processed with the eviews 10 program. The results of this study indicate that both partially and simultaneously EVA and MVA variables have a significant effect on returns. EVA has a higher influence than MVA. Abstrak. Penelitian ini dilakukan untuk mengetahui perkembang EVA, MVA, Return Saham dan pengaruh Economic Value Added dan Market Value Added terhadap return saham pada perusahaan manufaktur subsector food and beverage yang terdaftar di bursa efek Indonesia periode 2017-2020, baik secara parsial maupun simultan. Variabel bebas / independent variable pada penelitian ini adalah Economic Value Added (EVA) dan Market Value Added (MVA), sedangkan variabel terikat atau dependent variabel adalah return saham. Metode penelitian yang digunakan adalah metode kuantitatif, dengan regresi data panel dengan menggunakan metode common effect yang diproses dengan program eviews 10. Hasil penelitian ini menunjukan bahwa baik secara parsial dan simultan variabel EVA, MVA berpengaruh signifikan terhadap return. EVA memiliki pengaruh lebih tinggi dibanding MVA.